2000
DOI: 10.1080/000163500429343
|View full text |Cite
|
Sign up to set email alerts
|

Trends in reasons for tooth extractions in Norway from 1968 to 1998

Abstract: The aims of this study were (i) to determine the reasons for extraction of permanent teeth in Norway in 1998 and (ii) to describe changes in reasons for extraction in time-trend and quasi-longitudinal perspectives over 30 years based on three cross-sectional studies. The 1998 data were obtained from questionnaires distributed to a national random sample of 1,500 dentists, of whom 1,008 responded (67%). A total of 1,495 teeth were extracted for 1,164 patients (age 10-92 years) during a period of 2 weeks. Caries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 22 publications
5
50
1
4
Order By: Relevance
“…A reduced approximal bone level, using bite-wing radiographs, is regarded as the most common and valid indicator of destructive periodontal disease in all age groups. More importantly, the most common reason for tooth extraction (with the exception of third molars) in Norwegians aged > 45 years is periodontal disease [34], and the most common location for reduced number of teeth, as well as reduced bone level due to periodontal disease, is the premolar and molar regions of both jaws [35]. Moreover, it has been shown that partial recording protocols underestimate the prevalence of bone level changes [35].…”
Section: Discussionmentioning
confidence: 99%
“…A reduced approximal bone level, using bite-wing radiographs, is regarded as the most common and valid indicator of destructive periodontal disease in all age groups. More importantly, the most common reason for tooth extraction (with the exception of third molars) in Norwegians aged > 45 years is periodontal disease [34], and the most common location for reduced number of teeth, as well as reduced bone level due to periodontal disease, is the premolar and molar regions of both jaws [35]. Moreover, it has been shown that partial recording protocols underestimate the prevalence of bone level changes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed the trend that periodontal disease was the most frequent reason for tooth extraction in patients over 45 years of age as shown in previous studies. 3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Natural consequence of aging does not cause severe periodontal disease, and a small proportion of persons exhibit severe periodontitis in which tooth loss occurs. 22,23 Therefore, a large number of extractions might be extracted due to periodontal disease in a relatively small number of patients.…”
Section: Sex Age (Yr)mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] The main reasons for permanent tooth extraction differ among countries. Studies in many countries and some studies in small areas have shown that dental caries is the most common reason for tooth extraction.…”
mentioning
confidence: 99%
See 2 more Smart Citations